2021
DOI: 10.1188/21.cjon.647-654
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Participation: A Pilot Study of Patient-Identified Barriers

Abstract: Background: Little progress has been made in the past decade on improving clinical trial enrollment in the United States, particularly for adults and those in ethnic and racial minorities. Oncology nurses play a pivotal role in identifying and addressing patient concerns about clinical trials. Objectives: The aim was to identify patient-related barriers to clinical trial participation using a mixed-method patient survey and offer insights to develop evidence-based imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A patient and public involvement (PPI) approach to the trial development process, from the formulation of research questions to the dissemination of results, may help staff build trusting relationships with potential participants and foster mutual commitment [ 14 , 15 ]. If it can be demonstrated that participating in RCTs improves health status, this would encourage volunteers to take part in research and enable health professionals to be confident about inviting patients to engage in trials [ 16 , 17 ]. Evidence regarding the benefits of participating in RCTs may help to interpret the generalisability of research findings, aiding in the implementation of new interventions in clinical practice and healthcare policy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A patient and public involvement (PPI) approach to the trial development process, from the formulation of research questions to the dissemination of results, may help staff build trusting relationships with potential participants and foster mutual commitment [ 14 , 15 ]. If it can be demonstrated that participating in RCTs improves health status, this would encourage volunteers to take part in research and enable health professionals to be confident about inviting patients to engage in trials [ 16 , 17 ]. Evidence regarding the benefits of participating in RCTs may help to interpret the generalisability of research findings, aiding in the implementation of new interventions in clinical practice and healthcare policy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…McKinney and colleagues, as well as others, have suggested that the need for ancillary support to help clinicians identify patients who are eligible for clinical trials and educate eligible patients about trial procedures. [44][45][46] Such support is integral not only for ensuring patient engagement and education, but also to facilitate enrollment. Findings reported here highlight the value of persons who can provide ancillary support to clinicians for identifying patients who are eligible for clinical trials and in educating eligible patients about trial procedures as part of the enrollment process.…”
Section: Discussionmentioning
confidence: 99%
“…Of the patients who were reached, over a third agreed to participate in the current research study, and most study participants expressed interest in joining the trial. McKinney and colleagues, as well as others, have suggested that the need for ancillary support to help clinicians identify patients who are eligible for clinical trials and educate eligible patients about trial procedures 44–46 . Such support is integral not only for ensuring patient engagement and education, but also to facilitate enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…The survey demonstrated that one of the greatest challenges for patients was the cost of travel and time away from work. Prior studies have cited concerns related to ambiguity of treatment effectiveness, fear of adverse events, lack of control of treatment versus placebo, and time required for participation as major factors that impacted the decision to participate in a trial ( Brown, et al., 2013 ; McKinney et al., 2021 ). There was consistent messaging from patients that time away from work and overall cost remain a significant challenge.…”
Section: Discussionmentioning
confidence: 99%